2010
DOI: 10.1007/s00705-010-0819-5
|View full text |Cite
|
Sign up to set email alerts
|

Complete nucleotide sequences of a distinct bipartite begomovirus, bitter gourd yellow vein virus, infecting Momordica charantia

Abstract: Momordica charantia (Cucurbitaceae), a vegetable crop commonly cultivated throughout Pakistan, and begomoviruses, a serious threat to crop plants, are natives of tropical and subtropical regions of the world. Leaf samples of M. charantia with yellow vein symptoms typical of begomovirus infections and samples from apparently healthy plants were collected from areas around Lahore in 2004. Full-length clones of a bipartite begomovirus were isolated from symptomatic samples. The complete nucleotide sequences of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Present isolate BGYVV also formed group, showing closeness to Indian and Bangladesh isolates. Bitter gourd yellow vein virus (BGYVV) have been reported from several countries like Sri Lanka (Bandaranayake et al, 2014), Pakistan (Tahir et al, 2010a) and India (Mohanan and Sharma, 2020). Sequence comparisons revealed that the inter-specific recombination between Tomato leaf curl New Delhi virus and Tomato leaf curl PCR of the total DNA extracted from 153 samples were done.…”
Section: Resultsmentioning
confidence: 99%
“…Present isolate BGYVV also formed group, showing closeness to Indian and Bangladesh isolates. Bitter gourd yellow vein virus (BGYVV) have been reported from several countries like Sri Lanka (Bandaranayake et al, 2014), Pakistan (Tahir et al, 2010a) and India (Mohanan and Sharma, 2020). Sequence comparisons revealed that the inter-specific recombination between Tomato leaf curl New Delhi virus and Tomato leaf curl PCR of the total DNA extracted from 153 samples were done.…”
Section: Resultsmentioning
confidence: 99%
“…For isolates SOL and ACL primer pair WTGF/WTGR [ 20 ] were used to PCR amplify an approximately 1500 bp fragment spanning all of the intergenic region and most of the Rep gene (data not shown). A specific pair of abutting primers BGAF/BGAR [ 21 ] containing a unique restriction enzyme ( Apa 1) site, to PCR-amplify the complete begomovirus genome. The full-length begomovirus from isolate ABF was PCR-amplified with primer pair BF/BR [ 22 ].…”
Section: Methodsmentioning
confidence: 99%
“…The ORFs AC4 and AC5 however, presented some interesting comparisons. The AC4 ORF was 294 nt long and coded a putative protein of 97 aa similar to that in ToLCNDV (FN645905) and BGYVV (KJ862841), but it was only 177 nt long and encoded a product of 58 aa in all other viruses used for comparison (data not shown) except BGYVV (AM491590) in which it is truncated being only 126 nt long and encoding a protein with only 41 aa (Tahir et al, 2010).…”
Section: Comparison Of Orfs Sequencesmentioning
confidence: 96%
“…Ln1A has 96.3% similarity with another sequence KJ862841, available in data base under the name of BGYVV from Bangladesh. Interestingly, Tahir et al (2010) while analyzing the complete nt sequence of DNA-A (AM491590) of the begomovirus infecting bitter gourd (Momordica charantia), found it to have 94.4% similarity with ToLCNDV (FN645905) and named it along with latter as BGYVV. The existence of BGYVV as a distinct begomovirus species has however been questioned and deleted from the list of begomovirus species since it had 91% nt identity with ToLCNDV (AM747291) (http://talk.ictvonline.org/files/proposals/taxonomy_pro-posals_plant1/m/plant01/5307.aspx).…”
Section: Sequence Analysis and Characterization Of Genomementioning
confidence: 99%
See 1 more Smart Citation